EXPLORING UNEMPLOYMENT DYNAMICS IN EASTERN INDONESIA: PANEL REGRESSION APPROACH - Lailan Syafrina Hasibuan; Khaira Amalia Fachrudin (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
One of the biggest issues Eastern Indonesia faces is geographic isolation. There are limited employment marketplaces and economic prospects in this region because many areas are difficult to access due to inadequate transportation. Inadequate educational opportunities also contribute significantly to the problem of unemployment. Eastern Indonesia has several areas with poor educational infrastructure, which contributes to a low-skilled labor force. Furthermore, the unemployment issue is made worse by the difference in economic growth between Western and Eastern Indonesia. Sustainable Development Goals (SDGs) aim to eradicate poverty, safeguard the environment, and guarantee prosperity for all. SDG 8, which focuses on unemployment in this instance, addresses the topic of employment and good work for everyone. The aim of this research is to investigate the relationship between unemployment in Indonesia's Eastern Region and poverty, economic growth, and the human development index. investigated using the FEM approach and the panel data analysis method with the statistical program E-Views 10. According to the analysis's findings, unemployment is significantly impacted negatively by the human development index variable, positively and significantly by poverty, and not significantly impacted by economic growth.